ANALISIS TANTANGAN DAN PELUANG IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY DALAM DUNIA BISNIS DI INDONESIA - Nadila Rahma Wati; Ersi Sisdianto (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
Corporate Social Responsibility (CSR) has become an important component in today's business strategy, especially in Indonesia. This concept initially emerged to address the negative impacts of companies on the environment and society, but has now evolved into a strategic approach to support sustainability. This study aims to analyze the challenges and opportunities for implementing CSR in Indonesia, including the history of its development, the benefits generated, obstacles to implementation, and strategic opportunities in the era of globalization. Although regulated in laws and regulations, the implementation of CSR in Indonesia still experiences various obstacles such as lack of understanding of small and medium business actors, overlapping regulations and weak supervision. However, there are great opportunities for companies that are able to utilize CSR to create shared value and support the Sustainable Development Goals (SDGs). Effective CSR can be a major pillar of inclusive and sustainable economic growth.